The needs of relatives of intensive care patients during the transition from the intensive care unit to a general ward in China: a mixed methods study - Tianxiang Jiang; Hongyang Lu; Caiyan Su; Yangling Ge (BMC Nursing)
Abstract Background Relatives play an important role as caregivers in facilitating the recovery of their intensive care unit (ICU) patients during the transition period. Insight into the relatives’ needs is key to improving the continuum of transitional care and guiding family-centred high-quality health care services. This study aimed to comprehensively explore the needs of the relatives during the transition and to identify the factors influencing these needs in China. Methods This study adopted a mixed-method explanatory sequential design. The survey completed by relatives included needs levels, anxiety and depression levels, social support levels, and relocation stress levels. Qualitative data from semistructured interviews were collected after the survey to complement and explain the quantitative data. Twelve relatives were interviewed, and the qualitative data were analysed via thematic analysis. Results There were 161 valid responses and 12 relatives participated in unstructured face-to-face interviews. The present study identified a relatively high overall level of need. The highest overall mean scores on the need scale subscales were observed for communication needs, need for caregiving skills, and information needs. Six themes were identified: communication and access to information, caregiving guidance, emotional support, financial burden, information for a family care manual, and the comfort of the environment. The level of need was influenced by factors including age, educational attainment, caregiving experience, level of anxiety and depression, and level of relocation stress. Conclusion This mixed methods study identified in depth the needs of relatives during the transition period in China. This knowledge will help medical staff better understand relatives’ needs, recognize high-need target relatives and priority should be given to the implementation of tailored supportive care measures. Clinical trial number Not applicable.